Improving Crisis Management and Communication in Saudi Healthcare: The Contributions of Radiology and Nursing Specialists to Patient Safety - Yami, Mobarak Naji Mobarak Al; Ghubari, Mohammad Dhafer Al; Yami, Mahdi Naji Mobarak Al; Al-Musabi, Arwa Salem Abdullah; Al Saad, Zahrah Ali Saad; Alfahad, Reval Nasher Mohammad; Alshiban, Saeedah Hamad Hassan; Sharyah, Mahdi Ali Mohammed Al (Journal of International Crisis and Risk Communication Research, 2024)
Background: Patient safety is a critical focus in healthcare, aiming to minimize risks and harm through systemic efforts involving leadership, teamwork, and a culture of safety. Radiology departments face unique challenges due to their complex, high-tech nature, making safety culture essential. This study assesses Radiology and Nursing Specialists perceptions of patient safety culture, identifies areas for improvement, and raises awareness about safety practices in radiology. Methods: A descriptive cross-sectional design was used, employing a self-reported questionnaire based on the Survey on Patient Safety Culture. Data were collected from 171 Radiology and Nursing Specialists in public radiology departments, achieving a response rate of 46.5%. Positive perception percentages for 14 safety culture dimensions were calculated, with thematic analysis performed on qualitative feedback. Results: Positive perception rates varied from 34% to 81% across the dimensions. Strengths included "Teamwork within the unit" (81%), while areas for improvement included "Executive management support for patient safety" (34%), "Frequency of error reporting" (40%), and "Staffing" (44%). Qualitative feedback highlighted issues such as insufficient feedback mechanisms and staffing concerns. The overall safety rating averaged 2.45, indicating a "good" level of patient safety. Conclusion: The findings underscore the need for stronger management support, improved error reporting systems, and enhanced staffing to foster a robust patient safety culture. Addressing these areas could significantly enhance safety practices in radiology departments, benefiting both staff and patients. Future research should explore strategies for implementing these improvements effectively.